A Comprehensive Review of Integrated Energy Management for Future Smart Energy System - Ali, Md Shopan; Sharma, Anik; Joy, Tamal Ahammed; Halim, Md Abdul (Peneliti Teknologi Teknik Indonesia, 2024)
The main objective of this paper is to review the integration of energy management for future smart energy systems. The authors hope to address the developing landscape of energy management in the context of new smart energy systems in this review. The paper conducts a thorough review of integrated energy management methodologies that maximize energy generation, consumption, and distribution within these systems. The study assesses the multifarious solutions that enable effective and sustainable energy consumption by considering many components such as renewable energy sources, storage technologies, demand-side management, and grid interactions. The authors present insights into the problems and opportunities inherent in realizing the potential of future smart energy systems through an in-depth assessment of recent research, case studies, and advances in energy management. The assessment focuses on the inherent problems and opportunities associated with pursuing integrated energy management in smart energy systems. The application of cutting-edge sensing, communication, and control technologies to electrical grids has been studied to increase resilience, efficiency, and dependability. Real-time monitoring, analysis, and optimization of energy flows are made possible by the integration of cutting-edge sensors, communication systems, and control algorithms into electrical grids. Variable renewable energy sources, such solar PV and wind power, may now be seamlessly integrated into the grid thanks to advancements in renewable energy integration technologies. Case studies have shown how smart grid technologies can optimize energy management and save system costs. Integrating various DERs into grid operations has been the main focus of advancements in energy management. The paper navigates through the intricate considerations that stakeholders must make to maintain the resilience and sustainability of future energy systems, from dealing with the intermittent nature of renewable sources to maximizing energy dispatch mechanisms. The study reveals the revolutionary potential of a holistic approach to energy management by studying the changing role of digital technologies, data analytics, and predictive algorithms. Finally, this review contributes to a better knowledge of integrated energy management techniques, opening the path for a more robust, responsive, and environmentally friendly energy landscape.